RCCC calculations for electron scattering on quasi-two electron targets - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (Institute of Physics Publishing Ltd., 2012)
We report on the recent extension of the RCCC method to accommodate electron scattering from quasi-two electron targets. We present results for electron scattering from mercury (Z = 80) which serves as a testing ground for relativistic theories due to its high atomic number. Furthermore electron-mercury scattering plays an important practical role in the physics of fluorescent and high intensity discharge lamps.